Long‐Term Effects of Early‐Life Exposure to Environmental Oestrogens on Ovarian Function: Role of Epigenetics. (September 2014) - Cruz, G.; Foster, W.; Paredes, A.; Yi, K. D.; Uzumcu, M.
<x xml:space="preserve">Abstract</x> Oestrogens play an important role in development and function of the brain and reproductive tract. Accordingly, it is considered that developmental exposure to environmental oestrogens can disrupt neural and reproductive tract development, potentially resulting in long‐term alterations in neurobehaviour and reproductive function. Many chemicals have been shown to have oestrogenic activity, whereas others affect oestrogen production and turnover, resulting in the disruption of oestrogen signalling pathways. However, these mechanisms and the concentrations required to induce these effects cannot account for the myriad adverse effects of environmental toxicants on oestrogen‐sensitive target tissues. Hence, alternative mechanisms are assumed to underlie the adverse effects documented in experimental animal models and thus could be important to human health. In this review, the epigenetic regulation of gene expression is explored as a potential target of environmental toxicants including oestrogenic chemicals. We suggest that toxicant‐induced changes in epigenetic signatures are important mechanisms underlying the disruption of ovarian follicular development. In addition, we discuss how exposure to environmental oestrogens during early life can alter gene expression through effects on epigenetic control potentially leading to permanent changes in ovarian physiology.